Spatiotemporal variability of the chornozem soils humus - Pol’ovyi, A.; Mykytyuk, A.; Bozhko, L.; Barsukova, E.; Pylypyuk, V. (Scientific Progress & Innovations, 2022)
An assessment of the spatio-temporal variability of the humus content in the soil is presented, and a tendency of its decreasing in the agro-climatic regions of the Luhansk region is established. The cartograms of the humus content spatial distribution and the tendencies of changing its content in the soils of the Luhansk region for 20 years have been obtained. A very high humus content in the soil (from 4 to 6.5 %) is observed in the northern, central, and, partially, in the southern and eastern parts of the first agroclimatic region, where mainly thick and ordinary medium-humus chornozems are located in the loess rocks. In the rest of the territory, the humus content varies mainly from 2 to 4 %. In most of the territory of the second agroclimatic region, except for the southern strip, which stretches from the northwest to the southeast, the humus content in the soil is 3–4%, interspersed with those areas with high (up to 4–6 %) humus content. The soil covers of the third agroclimatic region are characterized by a great variety of soil types. In most of the region, there are ordinary crushed chernozems on the eluvium of the dense bedrocks with a predominant humus content of 2.5–4 %, and here, in a narrow strip (along the Anthracite – Sverdlovske line), there are powerful medium-humus chernozems on the loess rocks with a high content humus up to 4–6 %, a small part of them is also in the south of the region. In the eastern part of the district (to the east of the Lutugino – Krasnodon line), there are ordinary medium-thick medium-humus chernozems and ordinary low-power lowhumus chernozems, where the humus content is mainly 2–3.5 %. Over the years of surveys between 1987– 1991 and 2007–2011 against the background of sufficiently high humus content in the soil compared to the other regions of the Steppe zone of Ukraine, the decrease in the humus content in the first agroclimatic region was 0.49 % in absolute terms (89.62 % of the results of the first survey), in the second agroclimatic region – 0.29 % (92.45 % in relative values), in the third agroclimatic region – 0.1 % (97.48 % in relative values). The variation in the humus content in the soil is the smallest in the first agroclimatic region (the coefficient of variation is 15.37 %), where the soil cover is more uniform, it is somewhat larger in the second and third regions (the coefficient of variation is 20.0 and 20.67 %), where the soil cover is more variegated. The number of fields (cases) with a high humus content decreased, and the number with an average content, on the contrary, increased.